Focusing with colorectal cancer patients: a pilot study of a brief online group intervention - Gomes, Marta; Silva, Eunice R.; Salgado, João (Frontiers in Psychology, 2024)
Introduction Focusing-Oriented Psychotherapy has had a long history and influence on the field of psychotherapy. By “clearing a space” and “focusing,” individuals can enhance their emotional awareness and improve their ability to self-regulate. These tasks are particularly relevant in the context of Psycho-Oncology, although the research on their potential benefits for cancer patients is limited. Furthermore, the application of these tasks in a group or online setting has not been thoroughly explored. Methods This study aimed to examine the effectiveness of a two-session online intervention based on Focusing for cancer-diagnosed participants and its impact on their mental health and wellbeing. The study involved three participants with a diagnosis of colorectal cancer who were undergoing palliative treatment. We used both qualitative and quantitative methods. PFC-2 was used to assess participants' accomplishment of the task; FMS was used to assess the change in the focusing attitude, while CORE-OM, and PWBS-RV were used as mental health distress and psychological wellbeing measures; participant feedback was collected through questionnaires and a semi-structured interview. Results The results suggest that the tasks led to greater self-awareness, heightened self-reflection, and a sense of relief for the participants. Discussion These findings suggest that the group intervention protocol based on online Focusing sessions is potentially useful for broader applications.